The moral foundations for change management - Steare, Roger (Henry Stewart Talks, 2009)
You can change anything you like except fundamental organizational moral values -Organizations that behave in a way that undermines trust have and will risk everything -The ongoing destruction of corporate value is a consequence of a cynical destruction of moral values for short-term financial gain, Leading a culture of integrity isn't rocket science, its part of old wisdom and human nature